2002
DOI: 10.1074/jbc.c200228200
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative, ATP-dependent Association of the Nucleotide Binding Cassettes during the Catalytic Cycle of ATP-binding Cassette Transporters

Abstract: ATP-binding cassette (ABC) transporters harvest the energy present in cellular ATP to drive the translocation of a structurally diverse set of solutes across the membrane barriers of eubacteria, archaebacteria, and eukaryotes. The positively cooperative ATPase activity (Hill coefficient, 1.7) of a model soluble cassette of known structure, MJ0796, from Methanococcus jannaschii indicates that at least two binding sites participate in the catalytic reaction. Mutation of the catalytic base in MJ0796, E171Q, produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

40
349
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(395 citation statements)
references
References 29 publications
40
349
6
Order By: Relevance
“…However, recently, some interesting findings have contributed enormously to this field. First, Moody et al (2002) proposed that the Glu residue at the end of the Walker B sequence is the general or catalytic base of the NBD. This idea is based on the lack of measured ATPase activity when the Glu in question is mutated to Gln in MJ0796 and MJ1267 .…”
Section: Structural Aspectsmentioning
confidence: 99%
“…However, recently, some interesting findings have contributed enormously to this field. First, Moody et al (2002) proposed that the Glu residue at the end of the Walker B sequence is the general or catalytic base of the NBD. This idea is based on the lack of measured ATPase activity when the Glu in question is mutated to Gln in MJ0796 and MJ1267 .…”
Section: Structural Aspectsmentioning
confidence: 99%
“…The second lobe (arm II) forms an α-helical structure containing the C-loop and the Q-loop motif [28]. It was shown that in the presence of MgATP, the NBDs dimerize [9,36,57,63,82]. In this state, two ATP molecules are bound at the interface of two monomers and sandwiched between the Walker A and B motifs of one NBD and the C-loop of the opposite NBD.…”
Section: Functional Nonequivalence Of the Two Motor Domains Of Tapmentioning
confidence: 99%
“…Bacterial efflux ABC transporters transport a variety of solutes † This work was supported by grant GM070642 from the NIH. ATP (25;26). Also in the E. coli MsbA crystal structure, the NBD conserved Walker A domain is unresolved and the LSGGQ motif appears to be out of position for ATP hydrolysis since it must act in conjunction with the Walker A domain on the opposite monomer in order to bind ATP (Fig.…”
mentioning
confidence: 99%